OFFICIAL RELATIONS IN THE PERFORMANCE OF TECHNICAL INVESTIGATION, MAINTENANCE AND ORGANIZATION OF AIR TRAFFIC - Гусар, Ольга Анатоліївна; Літвінчук, Богдана Сергіївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: research of official relations in the implementation of technical investigation, maintenance and organization of air traffic. Research methods: analysis, synthesis, induction, deduction, analogy, comparison), from general scientific methods (empirical research, methods of theoretical knowledge) and formal-logical method of interpretation of law and comparative-legal method. The components of the methodological base are objectivity, a combination of critical and rational, constructive, comparative-retrospective approaches. Results: as a result of the study, the official relations arising in the structure of UkSATSE as the main body of air traffic services were considered. Public officials who carry out official relations in the aviation sphere to investigate events perform public functions that require specific knowledge and act as a link between the state and citizens. The basis for the technical investigation is to obtain from the subject of aviation or other sources of information about the event in the field of civil aviation. This event must be included in the List of events that must be notified by aviation entities. All bodies involved in the maintenance, organization and maintenance of air traffic are in constant contact, thereby entering into official relations, which is explained by the need to control some bodies to others, to facilitate the rapid detection that the aircraft is missing or missing. and for the purpose of effective functioning of the system of these bodies as a whole. UkSATSE Air Navigation Services organizes and interacts with related air traffic management bodies, UkSATSE, relevant management bodies of the Air Force of the Armed Forces of Ukraine, departmental air traffic management bodies.